Matrix approaches to approximate solutions of variational inequalities in Hilbert spaces. (2nd June 2016) - Cianciaruso, Filomena; Marino, Giuseppe; Muglia, Luigi; Xu, Hong-Kun
Abstract : A matrix approach to approximating solutions of variational inequalities in Hilbert spaces is introduced. This approach uses two matrices: one for iteration process and the other for regularization. Ergodicity and convergence (both weak and strong) are studied. Our methods combine new or well-known iterative methods (such as the original Mann's method) with regularized processes involved regular matrices in the sense of Toeplitz.